BETWEEN ACCURACY AND ALGORITHM: THE DOUBLE EDGE OF ARTIFICIAL INTELLIGENCE IN ACCOUNTING DECISIONS - Muhammad Miftahul Huda; Yusnaini (PT Wahana Global Education, 2025)
Artificial Intelligence (AI) has become an integral part of the accounting world, especially in the decision-making process. This research aims to analyze the influence of AI on accounting decisions by focusing on two main aspects: whether AI algorithms are able to reduce cognitive bias or create new risks. The method used in this research is Systematic Literature Review (SLR), with reference to 60 previous studies collected from various academic sources, such as Scopus, Google Scholar, Emerald, and SINTA. The results showed that AI has the potential to reduce cognitive bias in accounting decision-making by improving objectivity, efficiency, and data accuracy. However, the study also found that AI implementation is not free from new risks, such as algorithmic bias, lack of transparency, and over-reliance on technology. Factors such as data quality, algorithm design, and user understanding of AI are key elements in ensuring that this technology truly benefits the accounting process. The implications of this study emphasize the need for policy development that supports the ethical and transparent use of AI in accounting, as well as the importance of digital literacy for accountants in order to optimally utilize AI without setting aside critical considerations. Thus, AI can be an effective tool in improving the quality of accounting decisions without causing unintended negative impacts.